IMPULSE BUYING TENDENCY - hetharie, jondry adrin (SBM ITB, 2012)
This study has the objective to test stimulus which is given from store environment and store social factor toward impulse buying tendency mediated by positive emotion of consumers at Matahari departement store in Â Ambon City. This study is an explanatory research. Population of this study is consumers who shops in Matahari Department Store in Ambon City. With respondent for 128 people, sampling determination is using purposive sampling method. Data analysis technique in this study is using path analysis. Result of the analysis showed that there are direct effects from physical environment and social aspect of the store toward consumerâ??s positive emotion and toward impulse buying tendency. Result of this study also revealed that there are direct effects of consumerâ??s positive emotion toward impulse buying tendency and indirect effects of storeâ??s environment stimulus and storeâ??s social factor toward impulse buying tendency mediated by consumerâ??s positive emotion. Â Keywords: Positive Emotion, Impulse buying tendency